2020
DOI: 10.1007/s42452-020-2259-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of critical parameters on UHPFRC structural elements subjected to blast loading

Abstract: Response of structures subjected to blast loading is a highly complex phenomena involving time-dependent deformation, geometric and material nonlinearities and loading rate based material properties. During an explosion, blast loads act as an impulsive load of very short duration developing enormous heat and pressure. With increasing terrorist threats, attention is needed to study dynamic response of structures under blast loading. Ultra high strength concrete (UHPC) has been found to considerably enhance stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Rizwanullah and Sharma studied the role of critical parameters of UHPFRC structures under blast load. They concluded that compared to high strength concrete and normal concrete, UHPFRC increased capacity to disseminate a large amount of energy during blast loading and reduce the severe damage in the structure after blast load 19 . Mao 20 ,et al used the Concrete Damage Model in LS-DYNA to evaluate the behaviour of UHPFRC panels under blast loads, which took into account the strain rate effect.…”
Section: Introductionmentioning
confidence: 99%
“…Rizwanullah and Sharma studied the role of critical parameters of UHPFRC structures under blast load. They concluded that compared to high strength concrete and normal concrete, UHPFRC increased capacity to disseminate a large amount of energy during blast loading and reduce the severe damage in the structure after blast load 19 . Mao 20 ,et al used the Concrete Damage Model in LS-DYNA to evaluate the behaviour of UHPFRC panels under blast loads, which took into account the strain rate effect.…”
Section: Introductionmentioning
confidence: 99%